PENGARUH LINDUNG NILAI, FINANCIAL LEVERAGE, DAN MANAJEMEN LABA TERHADAP AGRESIVITAS PAJAK - Furqon Nurhandono; Amrie Firmansyah (Media Riset Akuntansi, Auditing & Informasi, 2017)
This research is aimed to provide empirical evidence about relationship between hedging, financial leverage, and earnings management on tax aggressiveness. Frank and Rego (2009) defines tax aggressiveness as the act of manipulation to reduce the amount of taxable income through tax planning efforts either it can or can not be categorized as an act of tax evasion. Using purposive sampling this research selected 24 firms that are listed in Indonesian Stock Exchange from 2011-2015 as samples. The result of multiple regression of panel data shows that there is positively significant relationship between financial leverage and tax aggressiveness as well as earnings management and tax aggressiveness. While there is no significant relationship between hedging and tax aggresiveness.